Penerapan Project Based Learning dalam Praktikum Teknologi Fermentasi di Sekolah Vokasi Institut Pertanian Bogor - Made Gayatri Anggarkasih; Ai Imas Faidoh Fatimah (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Fermentation technology is one of the subjects in the Food Quality Assurance Supervisor Study Program (SJMP), Vocational School, Bogor Agricultural University (IPB) which is given to semester IV students. Prior to the 2021/2022 academic year, practicum activities were carried out using the teacher centered method using practicum instructions in the form of modules prepared by lecturers, students only followed the modules and were not involved in practicum planning and designing experiments. Through this method, students are not given the opportunity to learn to think critically, creatively, and innovate. One way to optimize the achievement of learning outcomes is to apply the Project Based Learning (PjBL) model. The research was carried out using a one-shot case study method and a descriptive approach to 111 students of the Food Quality Assurance Supervisor Study Program in semester IV. The application of Project Based Learning in the fermentation technology course produces innovative products as project outputs, namely cinnamon yoghurt salad, cowpea tempeh nuggets, red gingerbread, sundubu jjigae with radish-based kimchi, steamed cakes of red dragon glutinous rice tape, braid donuts with fruit glaze Dragon, Dimsum Tempe Bogor Beans, and Frozen Sweet Corn Green Bean Yogurt. Of the 8 products, the panelists liked the red dragon skin glutinous tape steamed sponge cake the most (7.50), so it has the potential to be developed further, while the least preferred product was dimsum tempeh Bogor kacang (4.93). Based on the results of the questionnaire, 100% of students felt that Project Based Learning was effectively applied to fermentation technology courses, could increase motivation and interest in learning, and made it easier for students to understand the material. In addition, 99% of students feel optimistic about achieving competence in the field of food quality assurance, especially controlling fermented food production according to established competency standards, improving design skills and soft skills including teamwork, problem solving, and analytical skills.